MENGENALKAN ALAT MUSIK MELALUI MEDIA GAMBAR ANAK USIA DINI - Rizky Auliani; Hilyatul Ulya Najwa Afifah; Muawiyah Lani Panggabean; Hilda Zahra Lubis (LPPM Universitas Cipta Mandiri, 2024)
This research aims to introduce musical instruments to young children using image media. The subject of this research is Az-Zahra Kindergarten students. This research method uses descriptive research with a qualitative approach. The formulation of the research problem is how to introduce musical instruments to young children using picture media. The results of this research indicate that the use of image media is effective in introducing musical instruments to young children. Children demonstrate an increased understanding of various musical instruments and show high levels of interest during learning sessions. Image media helps build the basis of their introduction to musical instruments, creates positive associations, and stimulates curiosity about the world of music.